Adaptation or Persistence? Emergence and Revision of Organization Designs in New Ventures - Alexy, Oliver; Poetz, Katharina; Puranam, Phanish; Reitzig, Markus (Organization Science, 2021)
How organization designs evolve between adaptation to changing conditions and the pressures toward persistence of the designs adopted at founding remains an understudied phenomenon. To fill this lacuna, we conducted a longitudinal, multicase study of eight young ventures. We find that, in these ventures, specific organization design solutions changed frequently, triggered by various internal and external developments, although the changes were typically incremental and myopic. However, the more abstract principles of design, captured in the founders’ logics of organizing, were less amenable to change. This explains why observations of imprinting effects in logics of organizing may be consistent with observations of dynamic change to organization designs.